Newly trained lexical categories produce lateralized categorical perception of color - Zhou, Ke (National Academy of Sciences, 2010)
Linguistic categories have been shown to influence perceptual discrimination, to do so preferentially in the right visual field, to fail to do so when competing demands are made on verbal memory, and to vary with the color-term boundaries of different languages. However, because there are strong commonalities across languages in the placement of color-term boundaries, the question remains open whether observed categorical perception for color can be entirely a result of learned categories or may rely to some degree on innate ones. We show here that lateralized color categorical perception can be entirely the result of learned categories. In a visual search task, reaction times to targets were faster in the right than the left visual field when the target and distractor colors, initially sharing the same linguistic term (e.g., “blue”), became between-category colors after training (i.e., when two different shades of blue had each acquired a new name). A control group, whose conditions exactly matched those of the experimental group except that no new categories were introduced, did not show this effect, establishing that the effect was not dependent on increased familiarity with either the color stimuli or the task. The present results show beyond question that lateralized categorical perception of color can reflect strictly learned color categories, even artificially learned categories that violate both universal tendencies in color naming and the categorization pattern of the language of the subject.